Genetic and Serologic Properties of Zika Virus Associated with an Epidemic, Yap State, Micronesia, 2007 - Lanciotti, Robert S.; Kosoy, Olga L.; Laven, Janeen J.; Velez, Jason O.; Lambert, Amy J.; Johnson, Alison J.; Stanfield, Stephanie M.; Duffy, Mark R. (Emerging infectious diseases, 2008)
Zika virus (ZIKV) is a mosquito-borne flavivirus first isolated in Uganda from a sentinel monkey in 1947. Mosquito and sentinel animal surveillance studies have demonstrated that ZIKV is endemic to Africa and Southeast Asia, yet reported human cases are rare, with <10 cases reported in the literature. In June 2007, an epidemic of fever and rash associated with ZIKV was detected in Yap State, Federated States of Micronesia. We report the genetic and serologic properties of the ZIKV associated with this epidemic.